Eviota atriventris, a New Goby Previously Misidentified as Eviota pellucida Larson (Teleostei: Gobiidae) - Greenfield, David W.; Suzuki, Toshiyuki (Zootaxa, 2012)
A species commonly identified as Eviota pellucida in the literature has been misidentified and is in fact an undescribedspecies, described here as E. atriventris. Eviota pellucida is known only from the Gilbert and Marshall Islands, Ponape,Mariana Islands, and the Ryukyu Islands, Japan. Eviota atriventris is known from the Ryukyu Islands, Philippine Islands,Palau Islands, Indonesia, Papua New Guinea, Solomon Islands, New Caledonia, and the Great Barrier Reef, Australia. Eviota atriventris differs from E. pellucida in both preserved and live coloration and in pectoral-fin ray counts.